Factors associated with patient activation in an Australian population with comorbid diabetes and chronic kidney disease: a cross-sectional study. Issue 10 (22nd October 2017) - Zimbudzi, Edward; Lo, Clement; Ranasinha, Sanjeeva; Fulcher, Gregory R; Jan, Stephen; Kerr, Peter G; Polkinghorne, Kevan R; Russell, Grant; Walker, Rowan G; Zoungas, Sophia
Abstract : Objective: To evaluate the extent of patient activation and factors associated with activation in adults with comorbid diabetes and chronic kidney disease (CKD). Design: A cross-sectional study. Setting: Renal/diabetes clinics of four tertiary hospitals across the two largest states of Australia. Study population: Adult patients (over 18 years) with comorbid diabetes and CKD (estimated glomerular filtration rate <60 mL/min/1.73 m 2 ). Main outcome measures: Patients completed the Patient Activation Measure, the Kidney Disease Quality of Life and demographic and clinical data survey from January to December 2014. Factors associated with patient activation were examined using χ 2 or t-tests and linear regression. Results: Three hundred and five patients with median age of 68 (IQR 14.8) years were studied. They were evenly distributed across socioeconomic groups, stage of kidney disease and duration of diabetes but not gender. Approximately 46% reported low activation. In patients with low activation, the symptom/problem list, burden of kidney disease subscale and mental composite subscale scores were all significantly lower (all p<0.05). On multivariable analysis, factors associated with lower activation for all patients were older age, worse self-reported health in the burden of kidney disease subscale and lower self-care scores. Additionally, in men, worse self-reported health in the mental composite subscale was associated with lower activation and in women, worse self-reported health scores in the symptom problem list and greater renal impairment were associated with lower activation. Conclusion: Findings from this study suggest that levels of activation are low in patients with diabetes and CKD. Older age and worse self-reported health were associated with lower activation. This data may serve as the basis for the development of interventions needed to enhance activation and outcomes for patients with diabetes and CKD.